Moringa oleifera gum effect on blood sugar levels and rat pancreas histology induced by Streptozotocin - Utami, Eva Tyas; Fajariyah, Susantin; Lelono, Asmoro; Nihayah, Husnatun (STKIP Persada Khatulistiwa Sintang, 2024)
Moringa gum is a product that people can use as an anti-hyperglycemic agent. This study aimed to determine the effectiveness of Moringa gum in reducing blood sugar levels and improving the histology structure of the rat pancreas induced by streptozotocin (STZ). This study used 21 male rats divided into 3 groups including control, diabetes (STZ), and diabetes (STZ + 3% Moringa gum). STZ treatment at a single dose (45 mg/kg BW) was given intraperitoneally, while Moringa gum was given through drinking water for 2 weeks. Blood sugar levels were measured on days 0, 7th, 14th, 21st, and 28th. The results showed thatÂ STZ administration induced diabetes in rats with blood sugar levels of 487 mg/dL on the 14th day.Â Moringa gum administration was able to reduce blood sugar levels on days 21st and 28th respectively to 306 and 234 mg/dl. The histology structure of the pancreas of rats treated with gum also showed improvement. This study concludes that Moringa gum is effective in lowering blood sugar levels in rats even though it still does not show normal blood sugar levels, and can repair STZ-induced damage to the histology structure of the rat pancreas.